ANALISIS PENGARUH INOVASI PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DAN DAMPAKNYA TERHADAP KEPUASAN KONSUMEN - Walter Tabelessy (Soso-Q : Jurnal Manajemen, 2021)
This study aims to analyze the effect of Product Innovation and Promotion onPurchase Decisions and Their Impact on Consumer Satisfaction of CiptadentToothpaste in Ambon City. This research is a descriptive research. By using aquestionnaire as a data collection tool as many as 100 respondents. Sampling usingpurposive sampling. The data analysis method used is Partial least square usingsmartpls ver 3.0 which includes validity and reliability tests, as well as hypothesistesting and model evaluation tests. The results of the analysis show that productinnovation affects purchasing decisions, promotions affect purchasing decisions andpurchasing decisions affect consumer satisfaction.Keywords: Product Innovation, Promotion, Purchase Decision, Consumer Satisfaction